MIASTENIA GRAVIS: ETIOLOGI, PATOFISIOLOGI, MANIFESTASI KLINIS, PENEGAKKAN DIAGNOSIS DAN TATALAKSANA - KHAIRUNNISA SALSABILA; Hanna Mutiara; Rizki Hanriko (Medula, 2023)
Myasthenia gravis (MG) is an autoimmune disease characterized by fluctuating weakness of the extraocular, bulbar, and proximal muscles. Muscle weakness that occurs will worsen with activity and improve after rest. Myasthenia gravis is caused by the presence of autoantibodies on the postsynaptic membrane at the neuromuscular-junction (NMJ), such as antibodies against acetylcholine receptors, MuSK and LRP4. Myasthenia gravis is a rare neurological disease, the incidence is only about 1.7-21.3 per 1,000,000, has a bimodal distribution in women, with a peak of incidence at the age of 30-50 years. Men have a higher proportion after age 50. Myasthenia gravis is mostly a treatable disease but can result in significant morbidity and even death, so writing this literature review aims to discuss the pathophysiology, clinical manifestations, diagnosis and current treatment options for MG so as to increase the accuracy of the very early diagnosis. plays an important role in early management, as well as prevention of worse disease progression. The diagnosis of MG is based on anamnesis, neurological examination, electrodiagnostics, serology, and CT scan of the chest to see the presence of thymoma. The main treatment for MG is cholinesterase enzyme inhibitors and immunosuppressive agents. Symptoms that are resistant to primary treatment modalities or that require rapid resolution, such as in a myasthenic crisis, may require plasmapheresis or intravenous immunoglobulin treatment. Thymectomy can also be done.